Kinetic study on removal of heavy metal ions from aqueous solution by using soil - Lim, Soh Fong; Lee, Agnes Yung Weng (Springer, 2015)
In the present study, the feasibility of soil used as a low-cost adsorbent for the removal of Cu2+, Zn2+, and Pb2+ ions from aqueous solution was investigated. The kinetics for adsorption of the heavy metal ions from aqueous solution by soil was examined under batch mode. The influence of the contact time and initial concentration for the adsorption process at pH of 4.5, under a constant room temperature of 25± 1 °C were studied. The adsorption capacity of the three heavy metal ions from aqueous solution was decreased in order of Pb2+>Cu2+>Zn2+. The soil was characterized by Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopic-energy dispersive X-ray (SEM-EDX), and Brunauer, Emmett, and Teller (BET) surface area analyzer. From the FTIR analysis, the experimental data was corresponded to the peak changes of the spectra obtained before and after adsorption process. Studies on SEM-EDX showed distinct adsorption of the heavy metal ions and the mineral composition in the study areas were determined to be silica (SiO2), alumina (Al2O3), and iron(III) oxide (FeO3). A distinct decrease of the specific surface area and total pore volumes of the soil after adsorption was found from the BET analysis. The experimental results obtained were analyzed using four adsorption kinetic models, namely pseudofirst-order, pseudo-second-order, Elovich, and intraparticle diffusion. Evaluating the linear correlation coefficients, the kinetic studies showed that pseudo-second-order equation described the data appropriable than others. It was concluded that soil can be used as an effective adsorbent for removing Cu2+, Zn2+, and Pb2+ ions from aqueous solution.